2022
DOI: 10.1002/wene.438
|View full text |Cite
|
Sign up to set email alerts
|

Inferential‐ and measurement‐based methods to estimate rooftop “solar city” potential in megacity Seoul, South Korea

Abstract: Data analysis and collection techniques now allow for detailed inventory‐building of urban rooftops for the purposes of identifying solar energy potential within geographically defined boundaries, including those of cities. The complexity and inherent diversity of a city's building stock has propelled the introduction of many so‐called “solar city” assessment methods that, with varying levels of accuracy, scalability, and ease of use, seek to characterize the citywide solar photovoltaic (PV) resource potential… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 59 publications
(119 reference statements)
0
0
0
Order By: Relevance
“…A research study revealed a significant influence of the tree canopy on the estimation of street-level solar irradiation, in which the method could not fully capture the complex interactions of shadows cast by various urban elements such as trees and buildings [38][39][40]. Recently, studies [41][42][43] have suggested a method for the estimation of the potential annual energy production of PV systems on selected roofs in the regions of Skopje, the capital of North Macedonia, and Georgetown, the capital of Penang, respectively. The cited studies omitted the sitespecific impact on solar estimations and lacked a validation process to assess the accuracy of their results.…”
Section: Introductionmentioning
confidence: 99%
“…A research study revealed a significant influence of the tree canopy on the estimation of street-level solar irradiation, in which the method could not fully capture the complex interactions of shadows cast by various urban elements such as trees and buildings [38][39][40]. Recently, studies [41][42][43] have suggested a method for the estimation of the potential annual energy production of PV systems on selected roofs in the regions of Skopje, the capital of North Macedonia, and Georgetown, the capital of Penang, respectively. The cited studies omitted the sitespecific impact on solar estimations and lacked a validation process to assess the accuracy of their results.…”
Section: Introductionmentioning
confidence: 99%